2021
DOI: 10.1097/ccm.0000000000005232
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Outcomes of Hospitalized Children With Coronavirus Disease 2019: A Report From a Multicenter, Viral Infection and Respiratory Illness Universal Study (Coronavirus Disease 2019) Registry

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 40 publications
6
38
1
6
Order By: Relevance
“…Although fever, cough and rhinorrhea were the most common symptoms of children with severe COVID-19, we observed that the proportion of patients with cough and rhinorrhea was significantly lower than that of other respiratory viruses. The presence of cough was only reported in around one-third of children admitted to the ICU in a previous study ( 26 ). In our study, COVID-19 results in less severe disease when compared to other respiratory viruses, evidenced by the lower proportion of patients who required ICU admission, high flow nasal cannula/non-invasive ventilation, mechanical ventilation and empirical antibiotics.…”
Section: Discussionmentioning
confidence: 88%
“…Although fever, cough and rhinorrhea were the most common symptoms of children with severe COVID-19, we observed that the proportion of patients with cough and rhinorrhea was significantly lower than that of other respiratory viruses. The presence of cough was only reported in around one-third of children admitted to the ICU in a previous study ( 26 ). In our study, COVID-19 results in less severe disease when compared to other respiratory viruses, evidenced by the lower proportion of patients who required ICU admission, high flow nasal cannula/non-invasive ventilation, mechanical ventilation and empirical antibiotics.…”
Section: Discussionmentioning
confidence: 88%
“…Our study of critical paediatric COVID-19 from HICs and LMICs observed higher mortality than previously reported in large PICU studies and identified several factors associated with mortality. 4 , 6 , 7 Having a primarily respiratory illness was associated with higher mortality, while developing MIS-C or receiving treatments typically used for MIS-C was associated with lower mortality. Comorbid medical conditions were associated with higher mortality, both overall and in the subset of patients without MIS-C. Dexamethasone was not associated with improved mortality in any illness presentation or age group.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 Few studies focus on paediatric critical COVID-19, and most larger studies are from high-income countries (HICs). 4 , 5 , 6 , 7 Studies examining paediatric ICU (PICU) admissions from low-middle-income countries (LMICs) are scarce and generally focus on multisystem inflammatory syndrome in children (MIS-C). 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier, the impact of comorbidities on the severity of viral respiratory infections has been at the forefront during the COVID-19 pandemic. Comorbidities associated with severe COVID-19 include asthma, neurological disease, obesity, and diabetes [ 22 ]. For example, among 3221 SARS-CoV-2-positive children and adolescents enrolled in a global prospective cohort study with outcome data, 3.3% had severe outcomes within 14 days [ 23 ].…”
Section: Discussionmentioning
confidence: 99%